KONSENTRASI VFA DAN NH3 CAIRAN RUMEN DOMBA YANG DIBERI TEPUNG DAUN KELOR DAN MINYAK SAWIT SECARA IN VITRO - Safitri, Afifah Dian; Suhartati, F M; Rimbawanto, Efka Aris (ANGON: Journal of Animal Science and Technology, 2021)
Background. The research entitled VFA and NH3 Concentrations of Rumen Fluid Given In Vitro Moringa oleifera Leaf Meal and Palm Oil, which was conducted on 27 June 2020 to 12 September 2020. Materials and Methods. The material used in the study was the rumen fluid of 3 sheep obtained shortly after slughter, and beforehand lamb have been fed with the same treatment as the study. The treatment rations used consisted of R0 = control feed without moringa leaves and palm oil, R1 = control feed + 2% moringa oleifera leaf meal from feed dry matter (DM), and R2 = control feed + 2% moringa leaf meal from feed DM + 0.5% palm oil from feed DM. The method in the study was carried out in vitro according to Tilley and Terry (1963) which was modified by Sutardi (1979), the variable measured was the VFA concentration using the steam distillation method according to Krooman et al. (1967), while the rumen fluid NH3 concentration was measured using the Conway (1940) microdifusion technique. Results. The results of the analysis of variance showed that moringa leaf meal and palm oil supplementation had no significant effect (P> 0.05) on the VFA and NH3 concentrations of sheep rumen fluid in vitro, but the data obtained by supplementing Moringa leaf meal and palm oil could increase VFA 0,95% and NH3 0,94%. Conclusion. It was concluded that the use of 2% Moringa leaf powder supplementation and 0,5% palm oil increased the VFA concentration by 0,95% and NH3 0,94% of lamb rumen fluid in vitro. nd NH3 0,94% of lamb rumen fluid in vitro.